Proximity to natural habitat and flower plantings increases insect populations and pollination services in South African apple orchards. Issue 11 (22nd August 2021) - Ratto, Fabrizia; Steward, Peter; Sait, Steven M.; Pryke, James Stephen; Gaigher, Rene; Samways, Michael J.; Kunin, William
Abstract: Introducing areas of wildflower vegetation within crop fields has been shown to enhance pollinator activity and pollination services to crops, and findings in Europe showed an interaction effect between floral treatments and landscape context. Natural fynbos patches in the South African Cape Floristic Region (CFR) are potential reservoirs for beneficial insects that could enhance pollinator populations and crop pollination in commercial apple orchards. However, the effect of proximity to natural habitat and floral enhancement treatments on crop pollinators and yield are yet to be fully tested in southern temperate regions. To elucidate the impact of enhanced floral resources to apple flower visitors and crop yield, we established small experimental patches of flowers in non‐productive areas of commercial apple Malus domestica orchards in the CFR. Experimental orchards were embedded in landscapes with varying proportions of natural habitat within 1 km. We used pollinator exclusion experiments to determine the benefits of insect pollination on apple yield, quality and economic value. We found that the primary pollinator of apple flowers in the region is the endemic Cape honey bee, Apis mellifera capensis . Floral plantings enhanced overall pollinator abundance and honey bee flower visitation within the orchards, and positively affected apple size and economic value. Increased landscape complexity had a significantly positive effect on wild bees but not on honey bees. Synthesis and applications . We demonstrate that presence of floral plantings within orchards enhances pollinator activity within apple orchards and apple quality. This sustainable management practice may represent a profitable choice for growers, which could increase pollination services while reducing reliance on renting hives. These practices can indirectly contribute to increased landscape‐scale resilience and connectivity while also benefiting pollinators within the remaining natural habitat. Abstract : We demonstrate that presence of floral plantings within orchards enhances pollinator activity within apple orchards and apple quality. This sustainable management practice may represent a profitable choice for growers, which could increase pollination services while reducing reliance on renting hives. These practices can indirectly contribute to increased landscape‐scale resilience and connectivity while also benefiting pollinators within the remaining natural habitat.